Strategi Pengembangan Kewirausahaan UMKM di Kecamatan Pelalawan - Assyifa, Zubaidah; Hasda, Mifta; Zakir, Muhammad (Journal of Community Service and Empowerment, 2024)
This community service was carried out in Pelalawan District, Pelalawan Regency, Riau Province. The objects were MSMEs in Pelalawan District as partners of the Pelalawan District Religious Affairs Office in collaboration with the Riau Province Baznas in distributing Productive Zakat from BAZNAS Riau Province. This community service aims to develop entrepreneurial skills for MSMEs so that they can develop further than before. The results of this community service indicate that: 1) The success of the target number of training participants. 2) Achievement of activity objectives. 3) Achievement of planned material targets. 4) The ability of participants to master the material. Overall, this community service activity can be said to be successful. This success, in addition to being measured by the four components above, can also be seen from the interactive dialogue between participants and the community service providers where the community service providers provide the opportunity to ask as many questions as possible and provide answers that are quite satisfactory, as can be seen from the satisfaction of the participants after participating in the activity. The benefits obtained by participants are knowledge and understanding of the development of entrepreneurial skills possessed by participants.